Implementasi Rest Api Untuk Pencatatan Akta Kelahiran dan Kematian Pada Platform Web - Rahayu, Sri; Sutedi, Ade; Mutiara, Cahya (Institut Teknologi Garut, 2025)
Information and communication technology has evolved into a tool used to facilitate various tasks across society, including in civil registration services. However, in this study, issues were identified in the process of applying for birth and death certificates, as the current procedure remains complex and requires in-person visits to government offices with complete documentation. This research aims to develop a specialized application for birth and death certificate registration. The application will be integrated with village officers, thereby reducing the need for physical visits to government offices. The development of this application follows the Rational Unified Process (RUP) method, which involves four main phases: Inception, Elaboration, Construction, and Transition, and utilizes Unified Modeling Language (UML) for system architecture modeling, including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The resulting application is a web-based platform using REST API technology to connect with the population data server, and it is equipped with a notification service feature to facilitate message and information delivery to the public when applying for birth or death certificate services.